Migration Patterns of Upland Sandpipers in the Western Hemisphere - Hill, Jason M.; Sandercock, Brett K.; Renfrew, Rosalind B. (Frontiers in Ecology and Evolution, 2019)
Integrated models of the ecology of migratory species requires tracking of individual migratory organisms throughout the annual cycle. Here, we report the first information on the movement patterns of nine Upland Sandpipers (Bartramia longicauda) that were captured at breeding sites in Kansas and Massachusetts, and tracked with GPS and PTT tags to nonbreeding sites in South America. Upland Sandpipers were extreme migrants that regularly made nonstop flights that were >5,000 km in length and lasted up to 7 days. Sandpipers traveled up to 20,000 km per year in their annual movements. Our project resulted in a series of new discoveries. Sandpipers regularly crossed major ecological barriers during migration, which included long oceanic flights, high elevation mountains, and tropical forests. Migrating birds used known stopover sites in the central flyway of North America and eastern slope of the Andes in South America, and a subset of birds wintered in core nonbreeding sites in the Pampas ecoregion of Uruguay and Argentina. We documented new staging sites at canefields in the mountain valleys of Colombia, grasslands in the Llanos of Venezuela, and at airports along the Atlantic Coast of the US. Unexpectedly, some sandpipers spent the nonbreeding season on river islands in the Amazon basin, and pastures in the Cerrado ecoregion of Brazil; areas not previously known to host overwintering Upland Sandpipers. Like many other migratory birds in the Western Hemisphere, Upland Sandpipers had elliptical migration routes within the Southern Hemisphere, moved among separate activity areas during the nonbreeding season, migrated faster during southbound than northbound migration, and spent more time at nonbreeding than breeding sites. Collectively, the birds used sites across much of northern South America as a broad front migrant. Overall, the migratory patterns of Upland Sandpipers were more similar to migratory landbirds than to shorebirds that typically stage at wetlands and coastal estuaries. Upland Sandpipers should be buffered against habitat loss and degradation at local sites within their migratory range, but it may be difficult to protect specific sites or broad landscapes that would be needed to conserve a high percentage of the global population.